The Influence of Leadership Style, Work Ethic, and Job Satisfaction on the Performance of Local Government Office Employees - Samsul Arifin; Kuswandi Kuswandi; Sri Rahayu (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Optimal performance can be achieved when every individual in the organization works effectively and efficiently. This study aims to analyze the influence of leadership style, work ethic, and job satisfaction on employee performance at the Regional Office of the Directorate General of Taxes (Direktorat Jenderal Pajak/DJP) East Java II. The research sample consisted of 53 employees selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression methods. The partial test results show that leadership style does not significantly affect employee performance, whereas work ethic and job satisfaction have a positive and significant impact on employee performance. The simultaneous test results indicate that leadership style, work ethic, and job satisfaction collectively have a significant effect on employee performance. The coefficient of determination, at 71.1%, shows that leadership style, work ethic, and job satisfaction explain 71.1% of the variation in employee performance, while the remaining percentage is influenced by other factors not examined in this study. This study concludes that work ethic and job satisfaction play a crucial role in improving employee performance at the Regional Office of the Directorate General of Taxes (DJP) East Java II.